A novel nonviral gene delivery tool of BMP‐2 for the reconstitution of critical‐size bone defects in rats. Issue 10 (2nd June 2016) - Kolk, Andreas; Tischer, Thomas; Koch, Christian; Vogt, Stephan; Haller, Bernhard; Smeets, Ralf; Kreutzer, Kilian; Plank, Christian; Bissinger, Oliver
Abstract: The osseointegration of bone implants, implant failure, and the bridging of critical‐size bone defects are frequent clinical challenges. Deficiencies in endogenous bone healing can be resolved through the local administration of suitable recombinant growth factors (GFs). In preclinical models, gene‐therapy‐supported bone healing has proven promising for overcoming certain limitations of GFs. We report the dose‐dependent bridging of critical‐size mandibular bone defects (CSDs) in a rat model using a non‐viral BMP‐2‐encoding copolymer‐protected gene vector (pBMP‐2) embedded in poly(d, l ‐lactide) (PDLLA) coatings on titanium discs that were used to cover drill holes in the mandibles of 53 male Sprague Dawley rats. After sacrificing, the mandibles were subjected to micro‐computed tomography (µCT), micro‐radiography, histology, and fluorescence analyses to evaluate bone regeneration. pBMP‐2 in PDLLA‐coated titanium implants promoted partial bridging of bone defects within 14 days and complete defect healing within 112 days when the DNA dose per implant did not exceed 2.5 µg. No bridging was observed in untreated control CSDs. Thus, the delivery of plasmid DNA coding for BMP‐2 appears to be a potent method for controlled new‐bone formation with an inverse dose dependency. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2441–2455, 2016.